Pemberdayaan Masyarakat Melalui Sosialisasi Program Kuliah Kerja Nyata (KKN-PPM) di Kelurahan Kalirungkut Surabaya - Prihartanti, Wiwik; Hinyantari, Erlyna; H, Hardiono; Rahmanto, Agus; Suasridewi, Desak Gede; Febrihapsari, Mahardani; Kartika, Mira Gayatri; Gamal, Ahmad (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
The KKN-PPM program aims to: 1) Provide training and management of waste banks in the form of inorganic waste. This training provides knowledge and management in managing waste. Participants from Kalirungkut sub-district residents 2) Training in making carbolic acid. Training to produce carbolic acid is part of providing an increase in community income in the Kalirungkut sub-district, Surabaya. The approach used is the eco-efficiency (eco-development) model, synergistically combining ecological and economic components, to increase the entrepreneurial ability of the community. The result of this program is an increase in the community's ability to manage waste with economic value and is able to provide the community with the ability to produce carbolic acid which provides economic value. KKN-PPM activities have become a vehicle for the transfer of knowledge and technology between students who are doing KKN and the community together in increasing community empowerment to be able to prosper and enjoy a better income.